2018
DOI: 10.7287/peerj.preprints.26697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zeta potential of Escherichia coli DH5α grown in different growth media

Abstract: Proteins and metabolites typically adsorb to bacterial cell surface through a variety of mechanisms such as van der Waals attraction and electrostatic interactions, and forms a layer of nonspecifically adsorbed ions and molecules on the cell surface. Thus, the bacterial cell surface charge comprised the contribution from the cell wall as well as layers of nonspecifically adsorbed ions and molecules on the cell surface. This is the cell surface charge perceived by other bacterial cells in the growth medium. Giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The bacterial cell surface is generally negatively charged because of the carboxyl and phosphate core as well as the lipopolysaccharide (LPS) located at the surface [ 116 ]. E. coli surface charge is between −30 and −45 mV at milk pH [ 117 , 118 ]. While there are no published STEC-specific surface charge data generated with a modern instrument, some studies have shown that STEC isolates or reference strains are weakly negative [ 119 , 120 ].…”
Section: The Mechanism Of Stec-mfg Association: What Do We Know?mentioning
confidence: 99%
“…The bacterial cell surface is generally negatively charged because of the carboxyl and phosphate core as well as the lipopolysaccharide (LPS) located at the surface [ 116 ]. E. coli surface charge is between −30 and −45 mV at milk pH [ 117 , 118 ]. While there are no published STEC-specific surface charge data generated with a modern instrument, some studies have shown that STEC isolates or reference strains are weakly negative [ 119 , 120 ].…”
Section: The Mechanism Of Stec-mfg Association: What Do We Know?mentioning
confidence: 99%